Analisis Komposit Epoxy HGM Carbon Fiber dan Epoxy HGM Sisal Woven sebagai Material Rompi Anti Peluru - Bagus Kusuma; Elza Ully Tiara Tampubolon; Sovian Aritonang (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research examines the potential of Epoxy-HGM-Carbon Fibre and Epoxy HGM Sical Woven Fibre composites as alternative materials for bulletproof vests. These two materials were chosen because they have similar ballistic protection capabilities to kevlar but with lighter weight and more economical cost. Using the finite element method, this study simulates the resistance of each composite to the penetration and impact energy of projectiles in accordance with the NIJ 0101.06 standard to protect users from ballistic threats. The simulation results show that the Epoxy-HGM-S Sisal Woven Fibre specimen at an optimum thickness of 30 mm as well as Epoxy-HGM-Carbon Fibre at a thickness of 18 to 30 mm are able to meet the penetration, Back Face Signature (BFS), and residual kinetic energy criteria that comply with the safe limits for users. This research makes an important contribution to the identification of alternative materials that not only improve user comfort and mobility, but also maintain ballistic protection effectiveness for military and security applications, especially for personnel who need protection against ballistic projectiles.